Road traffic injuries and substance use among emergency department patients in the Dominican Republic and Peru - Cheryl J. Cherpitel; Jane Witbrodt; Yu Ye; Maristela G. Monteiro; Hernán Málaga; Jeannette Báez; Marisela Ponce de León Valdés (Pan American Health Organization, 2021)
Objective. To report demographic and substance use characteristics and risk of road traffic injury (RTI) from alcohol use, cannabis use, and combined use in a sample of emergency department patients from two countries in Latin America and the Caribbean. Methods. A cross-sectional study in which patients 18 years and older admitted within six hours of suffering an RTI to one emergency department in Santa Domingo, Dominican Republic (n = 501) and in Lima, Peru (n = 431) were interviewed. Case-crossover analysis, based on self-reported use prior to the RTI, was used to analyze risk from alcohol, cannabis, and co-use. Results. Overall, 15.3% reported alcohol use prior to the event and 2.5% cannabis use. Drivers using alcohol only were over twice as likely to have an RTI (OR = 2.46, p < 0.001), and nearly eight times more likely if using both alcohol and cannabis (OR = 6.89, p < 0.01), but risk was not elevated for cannabis alone. Significant differences were not found for passengers or pedestrians. Conclusions. Risk of RTI for drivers in these two samples is significantly elevated from alcohol use, and more so for co-use with cannabis. Differences between the two countries underscore the need for similar data from the region to determine risk of RTI from substance use, including risk for passengers and pedestrians. Data suggest that alcohol contributes significantly to the burden of RTI, which calls for more stringent enforcement of alcohol control policy related to drink driving in the region.